The effect of freezing on the characteristics of semifinished products in a dough covering using non-conventional protein-containing raw materials - Pasichnyi, Vasyl; Shubina, Yevgenia; Sviatnenko, Roman; Moroz, Olena (My University, 2022)
The relevance of this study is conditioned upon the increasing interest in alternative sources of protein, to solve the problem of providing the population with biologically complete food products of a combined composition. The purpose of this study was to investigate the effect of freezing on the stability of the moisture content of semifinished products in the dough covering using several types of meat raw materials, protein, and flour from hemp seed processing products. For the study, eight recipes of minced meat were prepared using beef, pork, red and white meat of broiler chickens with flour and protein from hemp seeds in the amount of 20% to the total mass of minced meat. In the samples, indicators of moisture content, moisture binding, emulsifying ability of products before freezing and after defrosting, and activity of water in defrosted products were determined. In the experimental samples, a substantial difference was found in the stability of the moisture content of semifinished products, depending on the combination of flour and hemp seed protein in the recipes of semifinished products and conventional types of meat raw materials under the influence of freezing. It was found that the best combination of hemp seed flour with beef and pork meat, while protein with broiler chicken meat is the best combination in terms of emulsifying ability. All model samples of minced meat had values above 40%, and all samples, except the combination of hemp protein with pork, were higher than the control. Studies of water activity values in defrosted dumplings were within the normal range of up to 0.970 Aw, and the sample using hemp seed protein and pork had the lowest – at 0.951 Aw. The conducted studies indicate the expediency of selective combination of hemp seed processing products with various types of meat raw materials in the composition of semifinished products in a dough covering. The combination of several types of non-conventional protein-containing raw materials in the composition of frozen semifinished products in the dough covering requires considering their technological compatibility to ensure the possibility of implementing the developed recipes in the production of dumplings in industrial production conditions
Keywords: кафедра технології м’яса і м’ясних продуктів; проблемна науково-дослідна лабораторія; борошно конопляне; рослинний білок; напівфабрикат заморожений; білоквмісна сировина; пельмені; hemp flour; vegetable protein; frozen semi-finished product; protein-containing raw materials; dumplings